2011
DOI: 10.1345/aph.1p503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Pharmacist-Directed Anticoagulation Service on the Quality and Safety of Heparin-Induced Thrombocytopenia Management

Abstract: Implementation of a focused inpatient PDAS was associated with improved efficiency of dosing, improved monitoring, and low bleeding risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…stopped and replaced with an alternative anticoagulant, which may be associated with a higher risk of bleeding and may be difficult to monitor [21,[25][26][27][28][29]. Our data showed that 20.9% of all samples referred for HIT investigation to a reference laboratory were positive in the EIA but negative in the SRA (presumed false-positive HIT test).…”
Section: Discussionmentioning
confidence: 79%
“…stopped and replaced with an alternative anticoagulant, which may be associated with a higher risk of bleeding and may be difficult to monitor [21,[25][26][27][28][29]. Our data showed that 20.9% of all samples referred for HIT investigation to a reference laboratory were positive in the EIA but negative in the SRA (presumed false-positive HIT test).…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, these drugs are sufficiently complex that many institutions have reassigned primary responsibility for their management to dedicated pharmacist-directed anticoagulation services. 89 Desirudin and fondaparinux offer hope of reducing therapeutic complexity. Neither appears to require routine laboratory monitoring or dose adjustment.…”
Section: Limitations Of Currently Available Agentsmentioning
confidence: 99%
“…When PDAS was not available, DTIs were managed by the other pharmacists, assuring a 24/7 coverage by a pharmacist. 15…”
Section: Study Methodsmentioning
confidence: 99%